2022
DOI: 10.4149/neo_2021_210823n1205
|View full text |Cite
|
Sign up to set email alerts
|

TRIM35 functions as a novel tumor suppressor in breast cancer by inducing cell apoptosis through ubiquitination of PDK1

Abstract: Breast cancer is the most common cancer in women. Novel mechanisms and targets are urgently needed to understand and treat this disease due to the complexity of breast cancer. I n this study, we evaluated the expression level of tripartite motif-containing (TRIM) 35 in various breast cancer cell lines by qPCR and immunoblot. Cell proliferation assay a nd flow cytometry were performed upon overexpression and depletion of TRIM35. Xenograft tumor model was applied to validate the findings observed in vitro. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…After inhibition of miR-10b, we observed a modest but significant reduction in cell metabolism, anchorage-independent growth, and proliferation, which associates with a significant increase in the expression of potentially novel candidate target genes of miR-10b: FANCC, SUN2, and TRIM35. All 3 of these genes have been implicated as tumor suppressors in other cancer types (25)(26)(27)(28)(29)(30)(31)(32). Overall, our results reveal a regulatory axis in FLC involving miR-10b to promote cellular proliferation.…”
Section: Introductionmentioning
confidence: 58%
“…After inhibition of miR-10b, we observed a modest but significant reduction in cell metabolism, anchorage-independent growth, and proliferation, which associates with a significant increase in the expression of potentially novel candidate target genes of miR-10b: FANCC, SUN2, and TRIM35. All 3 of these genes have been implicated as tumor suppressors in other cancer types (25)(26)(27)(28)(29)(30)(31)(32). Overall, our results reveal a regulatory axis in FLC involving miR-10b to promote cellular proliferation.…”
Section: Introductionmentioning
confidence: 58%
“…TRIM29 can bind to TIP60 and thus inhibit the acetylation of p53k120 mediated by TIP60, subsequently enhancing cell proliferation and malignant transformation (Sho et al, 2011). These above studies have shown that TRIMs can promote tumor proliferation; however, a small number of studies have revealed that some TRIMs act as tumor suppressors, such as Rong W and others have shown that TRIM35 inhibits the proliferation of breast cancer by enhancing the ubiquitination of PDK1 and inactivating AKT signaling pathway (Wang R. et al, 2022). Taken together, these results suggest that TRIMs are tightly involved in tumor proliferation (Table 2) (Supplementary Table S2).…”
Section: Name Ubiquitination Targetsmentioning
confidence: 95%
“…TRIM31 may promote BC progression by regulating the ubiquitination of p53 (Guo et al, 2021). Low TRIM35 expression was associated with poor prognosis of BC patients, and TRIM35 inactivated AKT signaling by increasing the ubiquitination of PDK1 to inhibit BC cell proliferation (Wang et al, 2022a). TRIM44 played a role in BC progression by promoting BC cell proliferation and migration through enhancing NF-κB signaling, and it was an independent prognostic factor for distant DFS and OS in patients (Kawabata et al, 2017).…”
Section: The Tripartite Motifs Protein Family In Colorectal Cancer (Crc)mentioning
confidence: 99%